ASSESSMENT OF TOURISTS PERCEPTION AND SATISFACTION OF TANZANIA DESTINATION - Philemon, John R. M. (European Scientific Journal, ESJ, 2015)
Tourism industry is very much affected with the perception that tourists carry with them about destination. Perceptions are always considered in relation to expectations and the dynamic nature of tourists’ perceptions calls for regular assessment. This is because they are the basis that tourists use to evaluate the quality of services that was delivered. This study thus aimed at assessing the international tourists’ perception on various attributes in Tanzania and examining their general satisfaction with Tanzania. It is quantitative in nature and utilized a survey research design. A total of 286 self-administered questionnaires were used in the analyses. These circuits are the Northern circuit (N), the Southern circuit (S), the Western Circuit (W), the Coastal circuit (C), and Zanzibar. Descriptive statistics (Frequencies, Percentages, Means, and Standard Deviations) and inferential statistics (one sample t-test) were performed to assess tourists’ perception and satisfaction with Tanzania on culture, wildlife, landscape, accommodation, restaurants, security and safety, infrastructure, and tour guidance. Findings shows that Tanzania is doing relatively well on the basic factor endowments such as culture, wildlife, landscape, and accommodation facilities, but fairly poor on tour guidance, tourism infrastructure, and restaurants. From a marketing managerial perspective, the findings should assist the tourism policy makers and practitioners to guide or develop tourists’ products by addressing areas where Tanzania as a destination has proven to be weak while improving further areas of strength which are basically the basic factor of endowments.